Penerapan Blended Learning Berbasis Numerasi dan Literasi untuk Meningkatkan Motivasi dan Hasil Belajar - Fadilah Falah Syifa; Mohamad Furqon; Ira Palupi Inayah; Muhammad Fadhil Hidayatullah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This research is motivated by the low motivation and learning outcomes of students in Informatics subjects, as well as the limited integration of numeracy and literacy skills in learning activities, especially at the Vocational High School (SMK) level. This has an impact on low active participation and student understanding of conceptual and applicable subject matter. The purpose of this study is to analyze the effect of the implementation of the Blended Learning model integrated with numeracy and literacy reinforcement on the motivation and learning outcomes of class X TJKT students at SMK Nurul Ulum Lebaksiu. This study uses a quantitative approach with a quasi-experimental design involving two groups, namely the experimental group and the control group. Data collection techniques were carried out through pretests and posttests, learning motivation questionnaires, and observations of learning activities. Data were analyzed using t-tests, multiple regression, and path analysis. The results showed that the implementation of the Blended Learning model significantly increased student learning motivation and learning outcomes compared to conventional learning. Students in the experimental group also showed a higher increase in mastery of numeracy and literacy skills. These findings indicate that a combination of online and offline learning, supported by a problem-based and project-based approach, can create a more effective, adaptive learning environment that meets the needs of today's students. This model is worthy of wider application in vocational education settings.